Peran Hutan Kota dalam Menurunkan Suhu Lingkungan dan Polusi Udara - Misbul Hadi; Madjid Ramadhana; Fauzan Syahmia; Salwa Mutiaa; Muhammad Ravia; Raja Amandaa; Abran Azizia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The Urban Heat Island (UHI) phenomenon occurs when temperatures in urban areas are significantly higher than those in surrounding rural regions. This is primarily caused by the concentration of buildings, vehicles, and human activities that generate and retain heat. As a result, cities become considerably warmer, especially during the daytime, leading to reduced thermal comfort and a decline in residents' quality of life. This study examines the role of urban forests in mitigating this issue. Using a literature review method, the researcher analyzed various scientific sources to understand how urban forests contribute to lowering ambient temperatures and improving air quality. The findings indicate that trees in urban environments can reduce air temperatures by approximately 1–8°C through shading and evapotranspiration. In addition, urban forests play a crucial role in absorbing carbon dioxide and mitigating the impacts of greenhouse gas emissions. The cooling effectiveness depends on factors such as tree species, canopy density, and the spatial arrangement of green spaces within the city. Therefore, the development and maintenance of urban forests represent an effective nature-based solution for creating cooler, healthier, and more sustainable cities in the face of increasingly extreme climate change.